Jains in the world : religious values and ideology in India - Cort, John E., 1953- (New Delhi Oxford University Press, 2001)
"This book presents a detailed fieldwork-based study of the ancient Indian religion of Jainism. Drawing on field research in northern Gujarat and on the study of both ancient Sanskrit and Prakrit and modern vernacular Jain religious literature, John Cort provides a rounded portrait of the religion as it is practiced today."--BOOK JACKET.
The ideology of the path to liberation -- Jains and Jainism in Patan -- Going to the temple: how to worship god -- Gifting and grace: patterns of lay-mendicant interaction -- Holy asceticism -- Remembrance and celebration: the Jain religious year -- Ideologies and realms of value.
Includes bibliographical references ( p. 237-256) and index.
Also available on the Internet to subscribing institutions.
Keywords: Jainism -- Doctrines; Religious life -- Jainism